Implementasi Pendidikan Masyarakat Berbasis Masjid untuk Muslimah di Desa Mattoanging Kabupaten Maros - Sri Ujiana Putri; Aswar Aswar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
The role of Muslim women in giving birth to quality is very much determined by the extent of the quality of the Muslim women themselves. The quality of these Muslim women will also be greatly determined by the extent to which the quality of education and guidance they receive. This view is the background of the KKN program in Mattoangin Village which aims to present various development programs for Muslim women based at the mosque as a form of efforts to improve the quality of civilization in the village of Mattoangin. The Muslim development programs that are carried out are: 1) Muslim taklim; 2) the learning process; 3) Ignore the reading of the Qur'an (Tahsin); 4) organizing corpse training; and 5) Muslimah Health Service. Each of them is described as follows. The results of this guidance for Muslim women are expected to provide a good understanding of the importance of improving personal qualities as a Muslim woman who will give birth to a quality of nation